Melon necrotic spot virus (MNSV): un nuevo virus en el cultivo de melon en Panama - Herrera Vasquez, J.A.=700 1 Cordoba Selles, M.C.; Jorda, C.
(Es, En)
Ilus., 29 ref.
Keywords: CUCUMIS MELO; CARMOVIRUS; VECTORES; OLPIDIUM; PANAMA; ELISA; RT-PCR